Development of E-LKS (Electronic Student Worksheets) Contain Hots (Higher Order Thinking Skills) Students in Science Learning - Fajarianigtyas, Dyah Ayu; Safin, Rievka Aprilina; Hidayat, Jefri Nur (Universitas Tidar, 2023)
Worksheet is one of the learning tools that plays an important role in students' thinking processes. The thinking process in achieving 21st century skills is that students can have higher order thinking skills (HOTS). The objectives of this research are: (1) How do teachers and students respond to the development of E-LKS which includes students' HOTS in science learning?, and (2) How to increase students' HOTS in using E-LKS in science learning? learning?. The research subjects were students of class VIII SMPN 4 Sumenep. This study uses the Research and Development approach and the four-dimensional research and development model by Thiagarajan. Our E-LKS validity data is obtained from Content Validity Index (CVI) analysis. Teacher and student response data were obtained by using response questionnaire analysis. Data on increasing HOTS in the use of E-LKS used pretest and posttest techniques with n-gain analysis. The results showed that the validity of the E-LKS on light materials and optical instruments class VIII was declared valid with a CVI score of 1.00 (very high validity) in terms of material and language aspects as well as media aspects. The results of teacher and student responses are in the positive category. The teacher's response to the E-LKS contains HOTS which is 96.97%, while the student response to the E-LKS contains HOTS which is 92.72% with the